Evaluation of in vitro antidiabetic and antioxidant characterizations of Elettaria cardamomum (L.) Maton (Zingiberaceae), Piper cubeba L. f. (Piperaceae), and Plumeria rubra L. (Apocynaceae) - Sh. Ahmed, Afnan; Ahmed, Qamar Uddin; Saxena, Anil Kumar; Jamal, Parveen (Pakistan Journal of Pharmaceutical Sciences, 2017)
Inhibition of intestinal α-amylase and α-glucosidase is an important strategy to regulate diabetes mellitus (DM). Antioxidants from plants are widely regarded in the prevention of diabetes. Fruits of Elettaria cardamomum (L.) Maton (Zingiberaceae) and Piper cubeba L. f. (Piperaceae) and flowers of Plumeria rubra L. (Apocynaceae) are traditionally used to cure DM in different countries. However, the role of these plants has been grossly under reported and is yet to receive proper scientific evaluation with respect to understand their traditional role in the management of diabetes especially as digestive enzymes inhibitors. Hence, methanol and aqueous extracts of the aforementioned plants were evaluated for their in vitro α-glucosidase and α-amylase inhibition at 1 mg/mL and quantification of their antioxidant properties (DPPH, FRAP tests, total phenolic and total flavonoids contents). In vitro optimization studies for the extracts were also performed to enhance in vitro biological activities. The % inhibition of α-glucosidase by the aqueous extracts of the fruits of E. cardamomum, P. cubeba and flowers of P. rubra were 10.41 (0.03), 95.19 (0.01), and -2.92 (0.03), while the methanol extracts exhibited % inhibition 13.73 (0.02), 92.77 (0.01), and -0.98 (0.01), respectively. The % inhibition of α-amylase by the aqueous extracts were 82.99 (0.01), 64.35 (0.01), and 20.28 (0.02), while the methanol extracts displayed % inhibition 39.93 (0.01), 31.06 (0.02), and 39.40 (0.01), respectively. Aqueous extracts displayed good in vitro antidiabetic and antioxidant activities. Moreover, in vitro optimization experiments helped to increase the α-glucosidase inhibitory activity of E. cardamomum. Our findings further justify the traditional claims of these plants as folk medicines to manage diabetes, however, through digestive enzymes inhibition effect.